WILL FOOD SECURITY BE AFFECTED BY RICE PRICE RISE - Akbarovich, Yadgarov Akram (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
The article analyzes the importance of ensuring food security today and the reasons for the increase in the price of rice in the world based on international statistical data